Vowel Harmony in Dogon Verbal Stems - (:unkn) unknown (My University, 2025)
Vowel Harmony in Dogon Verbal StemsThe purpose of this paper is to present further evidence in favor of a Proto-Dogon 10-vowel systemwith contrasts for [±ATR] at all heights, notably drawing upon comparative data from the other 20+related Dogon languages of Mali. Additionally, we report the first analysis of two vowel harmonyprocesses of the proto-language: progressive [ATR] and backness harmony.Vowel Harmony is widespread and varied among the Dogon languages; the direction of harmony andvowel quality have been the subject of debate. Hantgan et al. (2012; 2019; 2024) have analyzed theDogon language Bondu So as demonstrating bidirectional vowel-harmony and an underlying 10-vowelsystem with contrasts for [±ATR] at all heights /i ɪ e ɛ a a̟ ɔ o u/.Within this analysis, the typologically unusual [+High -ATR] /ɪ ʊ/ and [+Low +ATR] /a̘/ vowel phonemes surface as their more common counterparts [i u] and [a] respectively, resulting in a surface-true 7-vowel system. Evidence for the reduction of 10 underlying to seven surface contrasts is seen in the behavior of suffixal vowels on verbs and nouns. While mid-vowel suffixes transparently agree in[±ATR] with the value of the root vowel, roots containing high or low vowels are opaque. That is, astem-final mid vowel emerges as [ɛ e] or [ɔ o] depending on the underlying [±ATR] value of the rootvowel even though only [i u a] appear on the surface.Verbs in the Dogon languages are composed of a root, generally of a CVC shape accompanied by athematic TAM-marking stem vowel: -O for the imperative, -E for the perfective, underspecified -V inthe chaining form, etc. Table 1 illustrates the stability of mid root vowels’ progressive harmony.Dogon Language *téɡé DRIP *tómbé JUMP *kɛ́rɛ́BITE *dʒɔ̀bɔ́RUNBondu So téɡé tómbó kɛ́rɛ́ dʒɔ̀bɛ́Tommo So téɡé tómbó kɛ́rɛ́ dʒɔ̀bɔ́Yorno So téɡé tómɔ́ kɛ́rɛ́ dʒɔ̀bɔ́Tebul Ure téɡé tómbó cɛ́rɛ́ zɔ̀bɔ́Dogul Dom
Keywords: African Research